Impact of COVID-19 pandemic on Vascular Surgery Unit activity in Central Romania - Emil-Marian, Arbănași; Reka, Kaller; Vasile Adrian, Mureșan; Septimiu, Voidăzan; Eliza-Mihaela, Arbănași; Eliza, Russu (Frontiers in Surgery, 2022)
The COVID-19 outbreak has placed substantial pressure on the medical systems worldwide. This study aimed to investigate the influence of the pre-pandemic vs. the pandemic period on the activity of the Vascular Surgery Unit of a large Emergency Hospital in Eastern Europe. We performed a retrospective review of the vascular surgery cases admitted, comparing the statistics from the two time periods. We examined data on a total of 1693 patients over the two periods. We report a 34.51% decrease in the surgical procedures performed during the pandemic period, with a disproportionate number of 80.6% decrease in the number of cases admitted with a diagnosis of venous insufficiency diagnosis and an increase of 67.21% in the number of patients admitted with acute arterial ischemia. Furthermore, individuals not classed as emergencies were delayed or denied surgical care. The number of non-urgent procedures conducted by our Vascular Surgery Unit decreased significantly, whereas the number of emergencies surgeries increased. COVID-19's effect is projected to have a long-term impact on how surgical treatments are provided in Romania.